Пошаговое объяснение:
5х - 2 - 6 = 4 + 3х - 2
5х - 8 = 3х + 2
5х - 3х = 2 + 8
2х = 10
х = 10 : 2
х = 5
3х + 1 + 4 = 5х + 1 - 6
3х + 5 = 5х - 5
3х - 5х = -5 - 5
-2х = -10
х = -10 : (-2)
7 + 4х - 1 = 9х - 1 - 8
4х + 6 = 9х - 9
4х - 9х = -9 - 6
-5х = -15
х = -15 : (-5)
х = 3
5х + 4 - 6 = 3х + 4 + 8
5х - 2 = 3х + 12
5х - 3х = 12 + 2
2х = 14
х = 14 : 2
х = 7
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
5х - 2 - 6 = 4 + 3х - 2
5х - 8 = 3х + 2
5х - 3х = 2 + 8
2х = 10
х = 10 : 2
х = 5
3х + 1 + 4 = 5х + 1 - 6
3х + 5 = 5х - 5
3х - 5х = -5 - 5
-2х = -10
х = -10 : (-2)
х = 5
7 + 4х - 1 = 9х - 1 - 8
4х + 6 = 9х - 9
4х - 9х = -9 - 6
-5х = -15
х = -15 : (-5)
х = 3
5х + 4 - 6 = 3х + 4 + 8
5х - 2 = 3х + 12
5х - 3х = 12 + 2
2х = 14
х = 14 : 2
х = 7